A Facile Route to Prepare Hollow SiO2 Spheres Decorated with NiO Nanoparticles - Wang*, X.B.; Liu, J.; Xu, Z.D.; Li, J. (Asian Journal of Chemistry, 2011)
In this paper, the hollow SiO2 spheres decorated with NiO nanoparticles (denoted as SiO2/NiO hollow spheres) are successfully prepared using polystyrene (PS) spheres as hard template. At first, the PS-SiO2 core-shell structure is prepared by hydrolysis and condensation of tetraethyl orthosilicate (TEOS). Then the Ni source is incorporated by impregnation method. Finally, the SiO2/NiO hollow spheres are obtained by subsequent annealing process. The morphology of SiO2/NiO is hollow sphere with diameter of 1.5-2.5 μm by observation of scanning electron microscope and transmission electron microscope. Further investigation indicates that the NiO nanoparticles are dispersed on the shells of hollow spheres with diameter of 3-5 nm. Present work not only provides a facile route for preparation of SiO2/NiO hollow spheres, but gives an insight on the formation mechanism of hollow composite spheres.